The Association Between Anxiety Disorders and Insomnia Among College Students: A Cross-Sectional Study - Citra Puspa Juwita; Ezra Angela; Rosintan Milana Napitupulu (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Insomnia is a common sleep disorder in college students and one of the contibuting factors is the anxiety they experience in their daily lives. The purpose of this study was to determine the association between anxiety and insomnia in college students. A cross sectional design was used in this study to achieve the objectives, employing two valid and reliable questionnaires to represent the study variables. The first questionnaire, the Self Reporting Questionare (SRQ), is used to assess anxiety, and responding affirmatively to six or more questions is indicative of the presence of mental and emotional disorders . The second questionnaire is Insomnia Severity Index (ISI), which is utilized to assess insomnia. The population of this study consists of active undergraduate students enrolled at one private university in Jakarta. A total of 290 students are selected using accidental sampling techniques. Data are analyzed using The Chi Square test and the calculating of the Odds Ratio (OR) value through IBM SPSS 21 software. The prevalence of insomnia in this student population is found to be 83.1%, while the prevalence of anxiety is 57.2%. A significant association is identified between anxiety and insomnia (p < .001). Students who experience anxiety are found to be 7.1 times more likely to report insomnia compared to those who do not experience anxiety. This suggests that Anxiety, as one of the psychological disorders, has a strong influence on the sleep quality of college students, increasing their likelihood of developing insomnia by sevenfold. The findings of this study highlight a considerable co-occurrence of anxiety and insomnia among students. Further research is warranted to explore potential interventions that address both conditions simultaneously and to identify other factors that may contribute to sleep disturbances and psychological distress in the population. Keywords: Anxiety, College students, Insomnia, Sleep disorder